Analisis Pemahaman Masyarakat Nagari Batu Payuang Kecamatan Lareh Sago Halaban Tentang Zakat - Ana Kurnia (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The command to issue other people's rights in our assets or pay zakat, is contained in the pillars of Islam. The purpose of this discussion is to find out how the Nagari Batu Payuang community understands zakat and what factors influence the understanding of the Nagari Batu Payuang community regarding zakat. The research method that the author uses is (field research) field research with qualitative descriptive methods. The data collection technique that the writer used was field observation, interviews with the people of Nagari Batu Payuang and documentation. Data processing techniques are descriptive qualitative, namely collecting data related to the problem, then reading and analyzing then analyzing the data obtained with various theoretical foundations and finally drawing conclusions. As for the results of the research, the authors found that the community's understanding of Zakat, after conducting research, it turned out that there were as many as 10% who did not understand zakat related to zakat, and the other 80% understood zakat only in general terms and there were 10% who were able to understand zakat. Factors that influence this understanding include educational factors, economic factors, lack of counseling and lack of religious studies that address this issue of zakat